Analisis Perbandingan Algoritma Elias Gamma Codes Dengan Rice Codes Pada Kompresi File Gambar BMP - Marco, Ronal (Jurnal Sains dan Teknologi Informasi, 2024)
File compression is an important aspect in the development of information technology. The demand for providing information in a short time with a large number and size of files makes compression techniques important. Image files are files that have a lot of characters so they always cause problems with memory storage. There are many algorithms developed for file compression, namely the Huffman Algorithm, Goldbach Codes Algorithm, Elias Delta Codes, Elias Gamma Codes, and Rice Codes. In this research, a comparative analysis will be carried out between the two algorithms for image compression. The analysis carried out will compare the ratio of each algorithm in the image. The analysis results obtained in this research from bitmap files are that the Elias Gamma Codes algorithm has the best compression ratio with a Ratio of Compression (RC) value of 4.17, Compression Ratio (CR) of 28.5%, Redundancy of 71.4%, and Space Saving (Ss) of 72.5% compared to the Rice Codes Algorithm with a Ratio of Compression (RC) value of 2, Compression Ratio (CR) of 54.5%, Redundancy of 46.7%, and Space Saving (Ss ) of 45.5%.